Sarcopenic Obesity in Africa: A Call for Diagnostic Methods and Appropriate Interventions - Mendham, Amy E.; Lundin-Olsson, Lillemor; Goedecke, Julia H.; Micklesfield, Lisa K.; Christensen, Dirk L.; Gallagher, Iain J.; Myburgh, Kathryn H.; Odunitan-Wayas, Feyisayo A.; Lambert, Estelle V.; Kalula, Sebastiana; Hunter, Angus M.; Brooks, Naomi E. (Frontiers in Nutrition, 2021)
This perspective aims to address the issue of sarcopenic obesity in Africa and to highlight the lack of current knowledge on this topic. Sarcopenic obesity has been defined as obesity that occurs in combination with low muscle mass and function, which is typically evident in older adults. However there has been no clear consensus on population-specific diagnostic criterion, which includes both gold-standard measures that can be used in a more advanced health care system, and surrogate measures that can be used in low-income settings with limited resources and funding. Importantly, low and middle-income countries (LMICs) across Africa are in an ongoing state of economic and social transition, which has led to an increase in the ageing population, alongside the added burden of poverty, obesity, and associated co-morbidities. It is anticipated that alongside the increased prevalence of obesity, these countries will further experience an increase in age-related musculoskeletal diseases such as sarcopenia. Using the developmental origins of health and disease (DOHaD) approach will allow clinicians and researchers to consider developmental trajectories, and the influence of the environment, for targeting high-risk individuals and communities for treatment and/or prevention-based interventions that are implemented throughout all stages of the life course. Once a valid and reliable diagnostic criterion is developed, we can firstly assess the prevalence and burden of sarcopenic obesity in African based LMICs, and secondly, develop appropriate and sustainable interventions that target improved dietary and physical activity behaviours throughout the life course.